Agronomic characters and heritability of the third generation of Kampar mung bean lines (Vigna radiata) - DEWI INDRIYANI ROSLIM; TRESA NIA PRATIWI; HERMAN HERMAN (Smujo International, 2015)
Abstract. Roslim DI, Pratiwi TN, Herman. 2015. Agronomic characters and heritability of the third generation of Kampar mung bean lines (Vigna radiata). Nusantara Bioscience 7: 166-170. Kampar district is one of the mung bean producing areas in Riau Province, Indonesia. The low productivity of Kampar mung beans can be enhanced by doing plant selection in each generation to yield an expected superior line. The research aims to determine the agronomic character and heritability of third generation of Kampar mung bean lines. This research was conducted from October to December 2014 in the experimental garden of Biology, Faculty of Mathematics and Natural Sciences, University of Riau, Pekanbaru, Indonesia. It used nine lines of mung beans and five replicates with the Completely Randomized Design as design of experiments. Agronomic characters observed included plant height, number of productive branches, flowering time, 90% of harvesting time, number of pods per plant, weight of pods per plant, number of seeds per pod, seed weight per plant, weight of 100 seeds, pod color, and seed luster, Analysis of data uses analysis of variance (ANOVA) and if further significant differences are found, Duncan's Multiple Range Test (DMRT) will be carried out. The results showed significant difference for all the characters studied. All agronomic characters observed showed high heritability values, ranging from 0.92 to 0.98. G3 lines produce the highest number of pods per plant and highest number of seeds per pod and have small-sized seeds. G5 line has heaviest weight of pods per plant and heaviest weight of seeds per plant and they are in the criteria for medium-sized seeds. G1 lines’ seeds are classified as large seeds which are more superior to seeds of other lines. Therefore, lines of G1, G3, and G5 have the potential to be continued in the next generation because it is likely to contain potential sources of genes to get the superior Kampar lines mung bean.